Identity Declamation in Nigerien Oral Epic - Idé Oumarou, Adamou (Journal of Critical Studies in Language and Literature, 2021)
This paper examines identity through the declamation of zamu or praise poetry in the oral epic narration of Moumouni Sékou, one of the Zarma (an ethnic group from Niger) bards or griots better known as Kulba Baaba Seebeeri. Right at the opening episode of the epic song, the bard proceeds to exhibit the identity of one of his heroic figures Haamali Seyni Gakoy by announcing some of his qualities or values such as: fearlessness, truthfulness, friendliness, gorgeousness and self-control to name but a few. In the eyes of the griot, these traits are key values that characterize the identity of the noble. The exhibition of these salient and important qualities is an interpellation of the griot toward his audience, so as to make them aware of the cultural moral values that past generations held individually and collectively.